Why do we need a National Seniors Strategy? Because it’s 2016 - Samir Sinha (Law & Governance, 2017)
This letter is part of series of Open Letter essays from Canadian leaders in Healthcare. To see the complete series please click here.
Keywords: National Seniors Strategy, boomers, demographic shift, Senior, population health